The interaction between freezing tolerance and phenology in temperate deciduous trees - Vitasse, Yann; Lenz, Armando; Körner, Christian (Frontiers in Plant Science, 2014)
Temperate climates are defined by a distinct temperature seasonality with large and often unpredictable weather during any of the four seasons. To thrive in such climates, trees have to withstand a cold winter and the stochastic occurrence of freeze events during any time of the year. The physiological mechanisms trees adopt to escape, avoid and tolerate freezing temperatures include a cold acclimation in autumn, a dormancy period during winter (leafless in deciduous trees), and the maintenance of a certain freezing tolerance during dehardening in early spring. The change from one phase to the next is mediated by complex interactions between temperature and photoperiod. This review aims at providing an overview of the interplay between phenology of leaves and species-specific freezing resistance. First, we address the long-term evolutionary responses that enabled temperate trees to tolerate certain low temperature extremes. We provide evidence that short term acclimation of freezing resistance plays a crucial role both in dormant and active buds, including re-acclimation to cold conditions following warm spells. This ability declines to almost zero during leaf emergence. Second, we show that the risk that native temperate trees encounter freeze injuries is low and is confined to spring and underline that this risk might be altered by climate warming depending on species-specific phenological responses to environmental cues.